Characterization of water treatment sludge and its reuse as coagulant. (1st November 2016) - Ahmad, Tarique; Ahmad, Kafeel; Ahad, Abdul; Alam, Mehtab
Abstract: Coagulation-flocculation process results in the generation of large volume of waste or residue, known as water treatment sludge (WTS), in the purification of surface water for potable supplies. Sustainable management of the inevitable waste requires careful attention from the plant operators and sludge managers. In this study, WTS produced with the optimum alum dose of 30 ml/L at the laboratory scale has been treated with sulphuric acid to bring forth a product known as sludge reagent product (SRP). The performance of SRP is evaluated for its efficiency in removing the colloidal suspensions from the Yamuna river water over wide pH range of 2–13. 1% sludge acidified with sulphuric acid of normality 2.5 at the rate of 0.05 ml/ml sludge has been observed as the optimum condition for preparing SRP from WTS. The percentage turbidity removal is greater at higher pH value and increases with increasing the dosage of SRP. The optimum SRP dosage of 8 ml/L in the pH range of 6–8 performed well in removing the colloidal suspension and other impurities from the Yamuna water. The quality of treated water met the prescribed standards for most of the quality parameters. Thus, SRP has the potential to substitute the conventional coagulants partially or completely in the water treatment process, depending on the quality needed at the users end. Highlights: Optimum dose of alum for the treatment of Yamuna river water was determined. WTS produced at the optimum dose of alum was acidified to prepare SRP. SRP was used as a coagulant for the treatment of Yamuna water. Performance of SRP was evaluated in the pH range of 2–13 at variable dosage. Quality of the Yamuna water treated with optimum dose of alum and SRP was compared.